Facility Management and Urban Security - Pavlova–Traykova, Eli (Research Papers, 2018)
Essential for achieving a secure environment for work and living in cities is professional management of buildings and facilities. Current regulatory framework is used as a tool for achieving this security by facility managers. The current investigation analyzes existing legal frameworks related with natural hazards and accidents. Basic concepts and risk management levels are defined. Certain regulation and decrees are studied in details.
Keywords: Urban security; Facility management; Risk